Acculturation Is Related to Diet Quality in Phoenix Preschoolers, Controlling for Food Insecurity (P04-048-19) - Gutierrez, Marisa (Curr Dev Nutr, 2019)
OBJECTIVES: To examine the relationship between acculturation and diet quality of preschoolers in the Phoenix area. There is little research on how the dietary intake of preschoolers outside of the home is impacted by parental acculturation in food secure and insecure households. METHODS: This study was a cross-sectional secondary data analysis of the SAGE (Sustainability via Active Garden Education) research project. SAGE provides education on gardening, physical activity, and nutrition to preschoolers in Phoenix, AZ. Preschoolers (Mean age 53.1 + 3.5 mos; n = 154) were recruited from early care and education centers (ECEC). Acculturation was evaluated using a parent-report validated survey on a scale of 1–5 (1 = low acculturation). Parents also reported sociodemographic variables (child sex, age, ethnicity, and family income) and household food security status (dichotomized as food secure or insecure). Meals were observed by trained research staff at the ECEC for one full day (breakfast, lunch, snack) and recorded using the Nutrition Data System for Research. Linear regressions examined the relationship between acculturation and diet quality (total kcal, fruits, vegetables, saturated fat, added sugar intake) adjusting for sociodemographics and household food security status. RESULTS: A total of 78.6% of preschoolers in this study were Hispanic. Of the 154 children, 52.6% and 47.4% were male and female, respectively. The mean acculturation score was 3.0 + 1.3 with 41.8% of the sample being food insecure. Higher acculturation was significantly associated with increased vegetable (β = 0.095, P = 0.028) and saturated fat intake (β = 1.001, P = 0.018). Acculturation trended an association with increased kcal intake (β = 47.475, P = 0.053). CONCLUSIONS: Results suggest parent acculturation is associated with healthy and unhealthy eating habits in preschoolers outside of the home regardless of food security status. When evaluating diet quality of preschoolers, acculturation needs to be assessed to promote improved health behaviors, especially in relation to saturated fat and vegetable intake. FUNDING SOURCES: This study was funded by the Maternal Child Health Bureau and the National Institute of Minority Health and Health Disparities of the National Institutes of Health.